SCHOOL DISCIPLINE MANAGEMENT AS AN EFFORT TO IMPROVE POSITIVE BEHAVIOR OF STUDENTS AT SMP NEGERI 50 PEKANBARU - M. Fajri; Lila Sari Pohan; Suherman; Satri Widiyanti; Yuni Syafitri; Hendri Marhadi (SOSIOEDUKASI, 2025)
School discipline management plays a role as the main foundation in building student discipline in various learning activities at school. This study aims to describe and analyze the implementation of school discipline management as an effort to improve positive behavior of students at SMP Negeri 50 Pekanbaru. The research uses a qualitative approach with a case study design, which is a method that focuses on intensive exploration of positive behavior of students at SMP Negeri 50 Pekanbaru. Data collection was carried out through interviews, observations, and document analysis. The findings of the study show that the application of school discipline management to efforts to improve positive behavior of students at SMP Negeri 50 Pekanbaru can be seen from the behavior of students who, 1) respect each other, 2) take responsibility for actions, 3) honesty in action, 4) discipline in time management, 5) empathy and concern for others and the environment, 6) cooperate with each other in every activity, 7) there is participation and initiative. The conclusion of this study states that school discipline management can increase positive behavior of students at SMP Negeri 50 Pekanbaru.